2022
DOI: 10.1155/2022/4434887
|View full text |Cite
|
Sign up to set email alerts
|

PCMT1 Is a Potential Prognostic Biomarker and Is Correlated with Immune Infiltrates in Breast Cancer

Abstract: Background. Protein-L-isoaspartate (D-aspartate) O-methyltransferase (PCMT1) is involved in the occurrence and development of a variety of malignant tumors. However, the prognostic value of PCMT1 in breast cancer remains unclear. Methods. Based on the Cancer Genome Atlas database, we assessed the correlation between the expression of PCMT1 and prognosis, immune invasion, and tumor mutation burden in a variety of cancers. The expression level, mutation, immune correlation, and coexpression of PCMT1 in breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Two recent studies have shown that high expression level of PCMT1 is closely associated with poor prognosis of breast cancer patients (Guo et al., 2022; Zhang et al., 2023). Moreover, silencing PCMT1 expression effectively inhibits the proliferation and invasion of breast cancer cells and promotes apoptosis of them, so PCMT1 is also considered as a potential prognostic biomarker in breast cancer (Guo et al., 2022; Zhang et al., 2023). In this study, PCMT1 was also found to be significantly up‐regulated in breast cancer tissues and MCF‐7/PR cells and was associated with poor prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have shown that high expression level of PCMT1 is closely associated with poor prognosis of breast cancer patients (Guo et al., 2022; Zhang et al., 2023). Moreover, silencing PCMT1 expression effectively inhibits the proliferation and invasion of breast cancer cells and promotes apoptosis of them, so PCMT1 is also considered as a potential prognostic biomarker in breast cancer (Guo et al., 2022; Zhang et al., 2023). In this study, PCMT1 was also found to be significantly up‐regulated in breast cancer tissues and MCF‐7/PR cells and was associated with poor prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It presents high expression in tumor tissues and cells and thus is considered as prognostic biomarker for the above tumors. Two recent studies have shown that high expression level of PCMT1 is closely associated with poor prognosis of breast cancer patients (Guo et al., 2022; Zhang et al., 2023). Moreover, silencing PCMT1 expression effectively inhibits the proliferation and invasion of breast cancer cells and promotes apoptosis of them, so PCMT1 is also considered as a potential prognostic biomarker in breast cancer (Guo et al., 2022; Zhang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…PCMT1 is a member of the type 2 class of protein carboxyl methyltransferase enzymes. Studies show an association of elevated PCMT1 levels with various cancer types like breast cancer [ 69 , 70 , 71 , 72 , 73 , 74 ]. Another study constructing a genetic network for rheumatoid arthritis by evaluating genome-wide SNPs showed that PCMT1 is within the 41 identified significant SNPs, which is relevant to rheumatoid arthritis [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PCMT1 expression was signi cantly higher in hepatocellular carcinoma, bladder cancer, advanced-stage lung adenocarcinoma and metastatic ovarian cancer, and higher PCMT1 expression predicted poor prognosis of above malignant tumors [6,7,11,23]. Up to now, although it has showed that PCMT1 mRNA was highly expressed in BC, and the survival of BC patient with higher expression of PCMT1 was signi cantly poorer than those with lower expression [8][9][10]. However, no clinical information regarding the relationship between PCMT1 protein expression and clinicopathological characteristics of BC patients has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that higher PCMT1 protein expression is not only an unfavorable prognostic biomarker of surgically removed lung adenocarcinoma but also a predictive biomarker for poor prognosis of bladder cancer [6,7]. In addition, there are some researches showed that the outcome of BC patients with higher expression of PCMT1 gene was signi cantly poorer than those with lower expression [8][9][10].…”
Section: Introductionmentioning
confidence: 99%